Surgical techniques in orthopaedics anterior cruciate ligament reconstruction - Johnson, Donald; American Academy of Orthopaedic Surgeons (Rosemont : American Academy of Orthopaedic Surgeon, 2002)
In this program you will find multiple approaches, from different vantage points, using different graft materials and different fixation devices. In addition, this program shows how to prevent and how to correct common operative pitfalls and complications
Keywords: Anterior Cruciate Ligament -- surgery; Arthroscopy; Knee Joint -- surgery; Tendons -- transplantation